Peranan dan Manfaat BMT dalam Peningkatan Ekonomi Umat (Studi pada BMT At Taqwa Kabupaten Ciamis) - Edwin Hadiyan (Universitas Peradaban, 2015)
BMT or LKS is one of sharia business to avoid society from the danger of usury or commonly called interest, so that BMT becomes more fair and open which gives a sense of comfort to the custumer (small enterpreneurs) compared with the presence of conventional financial institutions that adopt the ribawi system. One of the goals and wisdom of the founding of BMT is to improve the welfare of the people, for that the managers of sharia financial institutions must be smart and smart looking for other sources of funds to increase capital financing for the needy.